Biology: a course for 'O' level - Kwan, Lam Peng; Hayward, Geoff (Federal Publications Singapore, 2000)
Biology: A Course for 'O' Level provides an accessible and structured approach to learning biology, covering key concepts and practical skills to help students excel in their O Level exams.